Enhanced thermal transportation across an electrostatic self-assembly of black phosphorene and boron nitride nanosheets in flexible composite films. Issue 27 (29th June 2022) - Wang, Yandong; Wei, Xianzhe; Cai, Huiwu; Zhang, Bin; Chen, Yapeng; Li, Maohua; Qin, Yue; Li, Linhong; Kong, Xiangdong; Gong, Ping; Chen, Huanyi; Ruan, Xinxin; et al.
Abstract : For effective heat dissipation in portable electronics, there is a great demand for lightweight and flexible films with superior thermal transport properties. Abstract : For effective heat dissipation in portable electronics, there is a great demand for lightweight and flexible films with superior thermal transport properties. Despite extensive efforts, enhancing the intrinsic low thermal conductivity of polymers while simultaneously maintaining their flexibility is difficult to achieve due to the dilemma of quarrying appropriate filler loading. Herein, a cellulose nanofiber-based film with high in-plane thermal conductivity up to 72.53 W m −1 K −1 was obtained by harnessing the advantage of functionalized boron nitride nanosheets ( f -BNNS) and black phosphorene (BP) via the vacuum filtration process. Besides, our unique design based on the electrostatic coupling of black phosphorene and functionalized boron nitride nanosheets significantly reduced the interfacial thermal resistance of the composite films. This work offers new insights into establishing a facile, yet efficient approach to preparing high thermal conductive heat spreaders.